Evaluation of road pavement resistance to traffic loads case study : (KH Abdul Halim street, Majalengka, Indonesia) - Ridho Fhaza Damar Yudha; Yusra Aulia Sari (LEADER: Civil Engineering and Architecture Journal, 2024)
Road pavement is an important part of transportation infrastructure that must be able to bear traffic loads effectively. Evaluation of road pavement resistance to traffic loads is crucial in ensuring road safety and reliability. This research aims to evaluate the performance of road pavement in withstanding loads from passing vehicles, with a focus on analysis of wear, deformation and structural resistance. The method used in the questionnaire may include questions regarding the driver's suggestions and hopes for improving road conditions. Data collected from this questionnaire is integrated with statistical analysis to identify factors that influence road pavement strength. research results on Jalan KH Abdul Halim Majalengka. This indicator has an average Importance of 4.48% and satisfaction of 2.23%. The implication of this research is to increase the safety of road users and extend the service life of road infrastructure.